A Discussion of Omics Integration in Harnessing Agricultural Waste: A Comprehensive Review on the Conversion of Empty Fruit Bunches into Biofertilizer - Teo, Chee Loong (Journal of Emerging Technologies and Industrial Applications, 2025)
Food waste valorization has gained increasing attention as a sustainable approach to mitigate environmental impacts and enhance resource efficiency in agricultural and industrial sectors. This review focuses on the integration of omics technologies—genomics, transcriptomics, proteomics, and metabolomics—in harnessing agricultural waste, particularly the conversion of Empty Fruit Bunches (EFB) from the palm oil industry into biofertilizer. The study explores the microbial communities, enzymatic processes, and metabolic pathways involved in EFB degradation and nutrient enrichment. Additionally, it discusses current challenges in food waste management, regulatory considerations, and industrial-scale applications of biofertilizers. The review highlights how integrating multi-omics approaches enhances the efficiency and effectiveness of biofertilizer production, contributing to circular economy practices and sustainable agriculture. Lastly, future research directions and potential policy interventions are proposed to standardize biofertilizer quality, optimize microbial consortia, and facilitate large-scale adoption. This work aims to provide comprehensive insights into innovative strategies for agricultural waste valorization and its role in environmental and economic sustainability.